Proposição de um modelo teórico dos influenciadores da atuação do profissional de educação física nos centros de atenção psicossocial - Silva, Sanderson Soares da (2023)
Introduction: In the search for the implementation and expansion of the psychosocial care model, some of the CAPS now have multidisciplinary teams in which Physical Education Professionals are included. However, different aspects seem to influence the performance of this professional and the use of body practices in mental health. Objectives: a) identify studies on the role of Physical Education Professionals and the use of body practices in Psychosocial Care Centers; b) analyze the perceptions of Physical Education Professionals at Psychosocial Care Centers regarding professional participation in work processes and the use of bodily practices in mental health care; c) propose a theoretical model of the influences of the Physical Education Professional's performance and the use of Body Practices in Psychosocial Care Centers. Methods: study 1: systematic review in which the data collection and presentation methodology followed PRISMA recommendations. Studies conducted in Psychosocial Care Centers in Brazil were included, which analyzed the PEF's performance from its own perspective, transversal or longitudinal; study 2: exploratory and descriptive study with a qualitative approach, in which PEF working in CAPS from different regions of the country were included. As an inclusion criterion, they should have worked for at least 90 days in mental health care. To collect data, a semi-structured interview was used, carried out remotely. To process the data, deductive content analysis was used; study 3: theoretical study, with the objective of proposing a model about the influencers of the PEF's performance in CAPS. This proposition was supported by a systematic review to describe the PEF's participation in the CAPS work process; then, based on the results of study 1, a semi-structured interview was constructed and used in this exploratory and descriptive study with 22 PEFs from different CAPS in the country. Finally, the construction of the model was created based on the content analysis of previous results. Results: study 1: 12 articles that met the inclusion criteria were included. All cross-sectional, qualitative studies and one study with a mixed approach. It was identified that the PEF does not participate in the entire work process in all units surveyed. In some of these, the action is restricted to the guidance of the PCs. In others, it participates in work processes such as reception, interconsultation and team meetings. It was possible to identify, in some cases, the use of the territory and the user's insertion in the community; study 2: the PEF's entry into CAPS is marked by opportunity, whether through a competition, directed by the NASF or Health Academy or political nomination. The lack of previous training for working in mental health was reported. Participation in work processes is diverse, in some units it participates in the entire work process, in others it only participates in core activities; study 3: the proposed model presents one main factor: the PEF and its performance in CAPS; and five factors external to it: professional training, physical and material structure, micropolitics, macropolitics of the service, territory resources and user needs. Final considerations: study 1: PEF participation does not occur in all stages of the work process in all CAPS, on the other hand, bodily practices in CAPS encourage autonomy and the use of the territory is a tool for deinstitutionalization and insertion of user in the community; study 2: there is a comprehensive and heterogeneous scenario of PEF's performance and the use of CP in CAPS. On the other hand, it is recommended to delve deeper into issues involving macro and micropolitical relationships in services to guarantee the consolidation of the psychosocial care model; study 3: This is the first study that summarizes the literature on the proposed topic and presents a synthetic theoretical model of the PEF's performance in CAPS.